Implementation of Zis (Zakat, Infaq and Shadaqah) to Improve the Welfare of Mustahik in Pamekasan Regency Based on Law No. 23 of 2011 Study on Zakat Collection Unit (Upz) IAIN Madura - Fatimatuz Zahroh; Herlin Fauzia Safitri; Meldona (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to understand and describe the application of Zakat, Infaq and Alms (ZIS) in improving the welfare of mustahik, especially in Pamekasan Regency through the IAIN Madura Zakat Collection Unit (UPZ). Poverty remains a major challenge faced by many countries, including Indonesia. Although various policies have been implemented to address this problem, their effectiveness often remains a key issue. The Zakat Collection Unit (UPZ) is one form of institution involved in managing zakat. The method used in this research is a qualitative approach with an interpretive paradigm, which emphasizes an in-depth understanding of experiences and social phenomena that occur in the field. The results of the discussion in this research 1) The implementation of Zakat, Infaq and Sadaqah (ZIS) in the IAIN Madura Zakat Collection Unit (UPZ) shows structured and effective efforts in managing social funds to help the community. UPZ plays an important role in collecting, distributing and disbursing funds to mustahik with a focus on transparency, accountability and efficiency. 2) Law Number 23 of 2011 concerning Management of Zakat, Infaq and Sadaqah (ZIS) provides an important legal framework for management and utilization of ZIS funds in Indonesia. UPZ IAIN Madura has implemented several programs to support the welfare of mustahik in Pamekasan Regency, such as Smart UPZ, Healthy UPZ, and Clean UPZ. UPZ IAIN Madura strives not only to meet the basic needs of mustahik but also to empower them through education and health. It is hoped that through this effort, stronger trust will be established between muzakki and UPZ, so that it can increase the amount and quality of assistance provided to mustahik in Pamekasan Regency.